DMAP: An Artifact for Identifying Scrum Antipatterns in Software Projects - Mosquera, Marcela; Flores, Pamela; Anchundia, Carlos E.; Segovia, Jorge; Valladares, Jimmy; Rocha, Evelin (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE); 2026: Anais do XXIX Congresso Ibero-Americano em Engenharia de Software, 2026)
Identifying software project management antipatterns in practice remains difficult because their evidence is often dispersed and hard to interpret. This paper presents DMAP, an artifact for detecting Scrum antipatterns and mapping them to management antipatterns. DMAP integrates a case-selection protocol, a dichotomous questionnaire, and an NPLF mapping scale. Evaluated on 164 case studies, the artifact selected 5 for detailed analysis and identified 7 Scrum antipatterns (12 occurrences) mapped to 5 management antipatterns. The results suggest that Scrum deviations can serve as indicators of underlying management problems.